Structural, Hirshfeld surface and in vitro cytotoxicity evaluation of five new N-aryl-N'-alkoxycarbonyl thiocarbamide derivatives - Pandey, Sunil K.; Pratap, Seema; Rai, Sunil K.; Marverti, Gaetano (Phosphorus Sulfur and Silicon and the Related Elements, 2020)
Five new compounds, N-(2, 4-dichlorophenyl)-N'-(methoxycarbonyl) thiocarbamide (1), N-(2, 4-dichlorophenyl)-N'-(ethoxycarbonyl) thiocarbamide (2), N-(2, 4-dichlorophenyl)-N'-(2, 2, 2-trichloroethoxycarbonyl) thiocarbamide (3), N-(2,4-dichlrophenyl)-N'-(pentoxycarbonyl) thiocarbamide (4) and N-(4-nitrophenyl)-N'-(pentoxycarbonyl) thiocarbamide (5), have been synthesized by the reaction of various alkoxy chloroformates with 2, 4-dichloroaniline/4-nitroaniline.The molecular structures of the compounds were elucidated by using spectroscopic methods (FT-IR, H-1 and C-13 NMR) and single-crystal X-ray structure analysis of compounds 2 and 5. Antiperiplanar orientation of C = O and C = S group across C-N bonds of thiocarbamide core may be due to the presence of intramolecular (N-H center dot center dot center dot O-C) hydrogen bond in the crystal structure of both the compounds. The presence of intermolecular interactions (C-H center dot center dot center dot S, C-H center dot center dot center dot O and N-H center dot center dot center dot S) in the molecular structure of the compounds has been studied in detail using Hirshfeld surfaces and their associated twodimensional fingerprint plots. In vitro cytotoxicity screening of the synthesized compounds evaluated on a panel of seven human cancer cell lines (cervical carcinoma (2008, C13*), colorectal (HT29 and HCT116) and ovarian carcinoma (A2780, A2780/CP and IGROV-1)) demonstrated significant inhibitory properties.
Keywords: Hirshfeld surface analysis; In vitro cytotoxicity; Thiocarbamide; X-ray crystal structure determination